Hydroxyethylcellulose use simplifies mat manufacture and improves interfacial cohesion of alkaline-treated Pandanus utilis fibres in polyester composite. Issue 4 (3rd April 2021) - Rafidison, Barisoa Harijaona; Ramasawmy, Hareenanden; Chummun, Jaykumar; Florens, François Benjamin Vincent
ABSTRACT: A simple method of bonding mutually perpendicular layers of alkaline-treated fibres, through the use of Hydroxyethylcellulose, has been studied as an alternative to woven fibre-mat. Following alkaline process optimisation by using the Taguchi DoE methodology, fibres treatment with 0.5% wt NaOH for 14 hours improved the tensile strength by 36% compared to the untreated fibres. Interfacial-Shear-Stress (measured by pull-out tests) was improved by 32% after the optimal alkaline-treatment. Furthermore, an improvement of 5% in Interfacial-Shear-Stress was achieved after a coating with 2 wt. % Hydroxyethylcellulose. Thus, Hydroxyethylcellulose increases the shear stress, and decreases friction without adverse impact on fibre strength.